Effects of 4 Weeks of a Technique-Specific Protocol with High-Intensity Intervals on General and Specific Physical Fitness in Taekwondo Athletes: An Inter-Individual Analysis - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The aim of this research was to compare the effects of a technique-specific high-intensity interval training (HIIT) protocol vs. traditional taekwondo training on physical fitness and body composition in taekwondo athletes, as well as to analyse the inter-individual response. Utilising a parallel controlled design, sixteen male and female athletes (five females and 11 males) were randomly divided into an experimental group (EG) that participated in the technique-specific HIIT and a control group (CG) that participated in traditional taekwondo training. Both groups trained three days/week for four weeks. Squat jump (SJ), countermovement jump (CMJ), 5-metre sprint (5M), 20-metre shuttle run (20MSR), taekwondo specific agility test (TSAT), multiple frequency speed of kick test (FSKTMULT), total kicks, and kick decrement index (KDI), as well as body composition were evaluated. Results indicate that there are no significant differences (p > 0.05) in the factors group and time factor and group by time interaction (p > 0.05). Although percentage and effect size increases were documented for post-intervention fitness components in TSAT, total kicks, KDI, and 20MSR, responders and non-responders were also documented. In conclusion, a HIIT protocol based on taekwondo-specific technical movements does not report significant differences in fitness and body composition compared to traditional taekwondo training, nor inter-individual differences between athletes. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.